2019
DOI: 10.3168/jds.2018-14733
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Source tracking Bacillus cereus in an extended-shelf-life milk processing plant using partial sequencing of rpoB and multilocus sequence typing

Abstract: We used rpoB partial sequencing and multilocus sequence typing (MLST) to characterize 7 Bacillus cereus strains obtained at the following points: ESL milk during shelf life, pasteurized milk, raw milk, and filler nozzles after cleaning in place. The objective of the study was to determine relatedness among B. cereus isolates from several sampling points along an ESL processing plant with the aim of source tracking. The study revealed that isolates from filler nozzles shared 100% similarity with isolates from E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…Biofilms are often blamed for quality problems in food and dairy processing, though they are difficult to find and accurately diagnose (Austin and Bergeron, 1995;Cherif-Antar et al, 2016). The lack of PPC reduction could also be because critical components of dairy processing equipment (e.g., filler nozzles) must be manually cleaned rather than undergo CIP, consistent with previous studies reporting filler nozzles as the likely source of repeat Pseudomonas (Ralyea et al, 1998) and Bacillus (Mugadza et al, 2019) contamination of fluid milk. Overall, it appears that enhanced sanitation chemistry cannot be relied upon as a panacea for eliminating PPC resulting from unknown or ambiguous contamination sources within a facility.…”
Section: S Rdna Findings Support That Specific Bacterial Taxonomic Groups Continued To Contribute To Ppc Even After Interventionssupporting
confidence: 57%
See 1 more Smart Citation
“…Biofilms are often blamed for quality problems in food and dairy processing, though they are difficult to find and accurately diagnose (Austin and Bergeron, 1995;Cherif-Antar et al, 2016). The lack of PPC reduction could also be because critical components of dairy processing equipment (e.g., filler nozzles) must be manually cleaned rather than undergo CIP, consistent with previous studies reporting filler nozzles as the likely source of repeat Pseudomonas (Ralyea et al, 1998) and Bacillus (Mugadza et al, 2019) contamination of fluid milk. Overall, it appears that enhanced sanitation chemistry cannot be relied upon as a panacea for eliminating PPC resulting from unknown or ambiguous contamination sources within a facility.…”
Section: S Rdna Findings Support That Specific Bacterial Taxonomic Groups Continued To Contribute To Ppc Even After Interventionssupporting
confidence: 57%
“…Alternatively, the lack of PPC reduction could have been observed even if behaviors were modified if employee behavior was not the primary source of the PPC. In previous studies, contaminated equipment has been identified as the source of PPC, but it is unclear if that contamination was the result of specific employee practices or a consequence of equipment structure, design, and cleanability (Eneroth et al, 2000a(Eneroth et al, , 2001Mugadza et al, 2019). Regardless of the root cause of the contamination, it is clear that facility management must be committed to ensuring that those they supervise comply with the practices set forth in training.…”
Section: Neither Training Alone Nor a Combination Of Training And Modified Cip Led To Reduced Occurrence Of Ppcmentioning
confidence: 99%
“…subtilis NCIB 3610 (raw milk), B. subtilis SRCM101392 (raw milk), B. subtilis SRCM103689 (raw milk), and B. subtilis SRCM103637 (packaged ESL milk). The result of a similar study with a focus on Bacillus cereus using the same milk samples implicates the aseptic filler-nozzle as a possible reservoir for these thermophilic spore formers during ESL milk processing (Mugadza et al, 2019).…”
Section: Country Of Originmentioning
confidence: 74%
“…When B. cereus spores adhere to filler nozzles, it may initiate biofilm formation which can lead to cross‐contamination of ESL milk products (Mugadza et al . 2019). Brooks and Flint (2008) described that routine CIP processes in the dairy industry may not always be sufficient to remove all bacterial cells that have attached to a surface, a notion corroborated by Khoza (2015).…”
Section: Discussionmentioning
confidence: 99%
“…Contaminating bacteria in ESL milk possibly originate from biofilms in the machine filler nozzles and are then dispensed into the final ESL milk during the filling process (Mugadza et al . 2019). Minimising biofilms has become a challenge for dairy manufacturers (Flint et al .…”
Section: Introductionmentioning
confidence: 99%